Distribusi Kandungan Logam Berat Pb dan Cd pada Sedimen Sepanjang Muara Sungai dan Laut Perairan Spermonde, Sulawesi Selatan, Indonesia - Rustiah, Waode; Noor, Alfian; Maming, Maming; Lukman, Muhammad; Nurfadillah, Nurfadillah (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
The determination of lead (Pb) and cadmium (Cd) levels in sediment samples in Spermonde waters has been determined. Sampling was carried out in river and sea estuary waters. The method used in the analysis of Pb and Cd is the one specified by SNI 06-6992.3-2004 and SNI 06-6992.4-2004. Based on the Decree of the Minister of Environment No. 51 of 2004, the general condition of Spermonde waters still supports the activities of marine organisms. The results showed that Spermonde waters received more Pb metal input than Cd metal. Pb metal content in river estuary and sea waters averaged 17.38 ppm. The highest Pb metal content is found in Lanjukang Island and Bone Tambung Island, each ranging from 20.88 ppm and 20.19 ppm. Meanwhile, the lowest Pb metal content on Barang Lompo island was 9.86 ppm. The detected metal content of Cd is only found in the Barrang Lompo and Kondong islands of Bali, each ranging from 1.04 ppm and 0.19 ppm, while the other locations Cd metal are undetectable. Based on the SQG value, the content of Pb and Cd in sediments in Spermonde waters is still in the standard range for sediment that has not been contaminated.